Analisis Pengaruh Laba Kotor, Laba Operasi, Laba Bersih, dan Modal Kerja Dalam Memprediksi Arus Kas Masa Mendatang (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2019-2021) - Suci Nurul Izzah; Nur Diana; Junaidi Junaidi (Universitas Islam Malang, 2023)
This research was conducted with the aim of knowing the Effect of Gross Profit, Operating Profit, Net Profit, and Working Capital in Predicting Cash Flow in the Future Empirical Study of Manufacturing Companies on the IDX for the 2019-2021 Period partially or simultaneously, and to find out which variables have a positive effect in predicting future cash flow in manufacturing companies listed on the Indonesia Stock Exchange. The data used in this study are secondary data and data collection is carried out by means of documentation, namely taking data from financial reports registered and published on the Indonesia Stock Exchange (IDX) from 2019-2021 and literature. This study uses multiple linear regression analysis techniques using the SPSS Version 22 application. This study shows that partially gross profit and working capital have a positive and significant effect in predicting future cash flow. While operating profit and net income have no significant effect in predicting future cash flow. Simultaneously gross profit, operating profit, net profit and working capital have a significant effect on future cash flow in infrastructure companies listed on the Indonesia Stock Exchange for the 2019-2021 period.Keywords : Gross profit, operating profit, net profit, working capital and cash flow